Review on Microbial Degradation of Aromatic Hydrocarbons: Focus on Kinetics Modelling - Umar, Z.D.; Yunusa, Y.R. (UMYU Journal of Microbiology Research, 2021)
Many anthropogenic activities produce huge quantities of chemical pollutants that find their ways into the natural environment. Those chemicals can either be of organic or inorganic sources, depending on their originating compounds. Over the years, there had been research findings regarding the application of microorganisms to provide solutions in the environment. This becomes imperative as salient issues in researches on microbial bioremediation will be understood. This review focused more on Kinetics modeling during biodegradation of aromatic hydrocarbons and their nature and effect on the environment coupled with the conventional remediation techniques. Kinetics modeling during bioremediation predicts microbial activities through their mechanism of actions towards the targeted contaminants. This gives better understanding of the rate of chemical degradation through different variable parameters. Modeling the cultivation of degrading organisms can highlight the inhibitory properties of the cells involved. Therefore, specific microbial growth rates can be modeled at various initial concentrations of the involving substrates. Such could be achieved using secondary models of Monod, Teissier, Aiba, Haldane, Yano and Luong. The models can reveal the substrate inhibitory effects to the reduction rate (as in the case of Monod) or inhibitory to the substrate rates like in the other models. Many studies were recently conducted on modeling microbial growth. Hence, utilization of those models are the best evidence that indicate when the substrates are toxic or inhibitory to the microbes. This provides better understanding on the future researches regarding the bioremediation effectiveness on scientific arguments.